Workforce Participation, Ageing, and Economic Welfare: New Empirical Evidence on Complex Patterns across the European Union - Mirela S. Cristea; Marilen G. Pirtea; Marta C. Suciu; Gratiela G. Noja (Complexity)
The ageing population has become one of the major issues, with manifold consequences upon the economic welfare and elderly living standards satisfaction. This paper grasps an in-depth assessment framework of the ageing phenomenon in connection with the labor market, with significant implications upon economic welfare, across the European Union (EU–27). We configure our research on four distinctive groups of the EU–27 countries based on the Active Ageing Index mapping, during 1995–2018, by acknowledging the different intensities of ageing implications on economic well-being from one group of countries to another. The methodological endeavor is based on Structural Equation Modelling. Empirical results highlight that the ageing dimensions and labor market productivity notably shape the socioeconomic development of EU countries, visibly distinguished across the four panels. The economic development induced remarkable positive spillover effects on the welfare of older people, under the influence of the ageing credentials and dynamic shaping factors. Our research advances the literature underpinnings on this multifaceted topic by investigation made on specific groups of the EU countries and distinctive strategies proposed for each group of countries, as effective results for improving the well-being of older people. Constant policy rethinking and adequate strategies should be a top priority for each specific group of EU countries, to further sustain the ageing phenomenon, with positive implications mostly on elderly welfare.